Physical functioning and rehabilitative needs across the cancer continuum in patients with oesophageal cancer - Gannon, Jenny (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2016)
In recent decades, the incidence of oesophageal adenocarcinoma has dramatically increased, particularly in developed countries. Treatment for oesophageal cancer has traditionally been associated with poor outcomes and consequently a poor prognosis, however morbidity and mortality rates, in addition to long term survival post oesphagectomy have all dramatically improved over the past two decades. Notwithstanding progress in survivorship, curative treatments are complex and remain associated with risks of morbidity and mortality. Major surgery, in combination with preoperative chemotherapy and radiotherapy, can have an attritional impact on physical functioning. Poor physical functioning is associated with decreased overall HRQOL and an increased risk of disability and therefore is an important outcome to measure in any population. A systematic review of the literature was carried to investigate the impact of curative treatment for oesophageal cancer on subjective and objective measures of physical functioning. Both neoadjuvant therapy and oesophagectomy were shown to have a significant negative impact on physical functioning in the acute phase post treatment. However there were inconsistencies in the literature regarding the long term recovery of physical functioning after successful completion of treatment for oesophageal cancer. In Study 1 in this thesis, survivors of oesophageal cancer (11-36 months post surgery) demonstrated significantly lower fitness and physical activity levels than age and gender matched control participants. A medical record review conducted as part of Study 1 revealed that the study cohort experienced a decrease in body weight and BMI at one, three and six months post-operatively with body weight continuing to be decreased up to three years post surgery. In addition, over 30% of the total study cohort was classified as sarcopenic prior to surgery. The second study in this thesis (Study 2) involved a qualitative exploration of the impact of treatment on physical functioning from the perspectives of survivors who were one to five years post surgery. This study aimed to further explore the potential reasons for the suboptimal physical functioning observed in Study 1 and to provide a more in-depth and contextualised understanding of the patient experience and patient needs. Participants in Study 2 reported physical changes and side effects of treatment which had impacted on their physical functioning and lifestyle. This cohort had poor knowledge and awareness of physical activity guidelines and the wide ranging benefits of exercise and faced a number of disease specific and general barriers to exercise and optimal activity levels. Overall Study 1 and Study 2 demonstrated the significant adverse impact treatment for oesophageal cancer can have on physical functioning, which can persist up to five years post-operatively. These findings provide data that suggest that a comprehensive multidisciplinary rehabilitation programme may be a promising intervention to improve physical performance and HRQOL in survivorship. Study 2 examined participants’ views on the development of such a programme. Participants expressed a high level of interest in rehabilitation and stated that they thought it would be beneficial for survivors of oesophageal cancer. Therefore interventional programmes appear feasible and would be well received in an oesophageal cancer population post completion of treatment. In order to investigate when changes in physical functioning may occur across the cancer continuum, the third study in this thesis (Study 3) prospectively measured the acute impact of curative multimodal treatment for oesophageal cancer on physical performance. The preliminary results from this ongoing study suggest that oesophagectomy has a marked adverse impact on physical functioning but that chemotherapy and radiotherapy have a lesser impact. Fitness, hand grip strength and physical activity levels remained the same during neoadjuvant treatment. However a significant loss of hand grip strength was observed in participants four weeks post oesophagectomy as compared to baseline measures. Similarly, a clinically meaningful decrease in fitness levels was observed from pre surgery to four weeks post surgery. In addition, this study recorded low physical activity levels across the study period; at diagnosis, post neoadjuvant treatment and four weeks post surgery. The final study in this thesis, Study 4, qualitatively explored the patients’ perspectives on their physical functioning from diagnosis and throughout their neoadjuvant treatment. This study gave a more in-depth evaluation of the impact of chemotherapy and radiotherapy on physical functioning and revealed that for most participants, neoadjuvant treatment did have some impact on physical functioning. However the majority of participants reported that the physical impact of neoadjuvant treatment was reasonably temporary and self limiting. While the objective measures of strength, fitness and physical activity levels were not significantly affected by chemotherapy and radiotherapy in Study 4, these measures were already low at diagnosis. As a result, this cohort may be an increased risk of post-operative complications. A prehabilitation intervention that would improve strength, physical activity and fitness pre-operatively may positively influence these complications. Study 2 examined participants’ views on the development of a prehabilitation programme and the results overall indicated that a programme would be feasible between diagnosis and surgery. An important finding of this study however, was that the side effects of neoadjuvant treatment were experienced to varying degrees and at different times by participants. Therefore timing of interventions may have to be varied according to a patient’s response to therapy and reasonably flexible in terms of timing, structure and components.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin